FATIGUE LIFE ANALYSIS OF RAMP DOOR FERRY RO-RO GT 1500 USING FINITE ELEMENT METHOD - Alam, Alamsyah; A. B. Mapangandro; Amalia Ika W; M U Pawara (Deputi TIRBR-BPPT, 2021)
Ro - Ro Ferry is equipped with a connecting door between the port and the ship. The ramp door experiences load during loading and discharging of the rolling cargo. This repetitive load may cause fatigue failure. The structure of the ramp door should withstand this load. Therefore, The ramp door should be properly designed to ensure the structural integrity of the ramp door. The purpose of this research is to analyze the maximum stress and the Fatigue life of the bow ramp door. The method used is the finite element method. The given loads are several types of vehicles that are commonly transported by the ship. The given load case is the point load working at the girder plate and between the girder plate. Based on the simulation results with the given point load, the maximum stress is identified located between the girder for the large truck case with 397.02 MPa, while the minimum stress located at the girder for sedan car with 43.93 MPa. As for the fatigue life of the bow ramp door construction. it is 1.17 398.64 years, and the load cycle is 5.35 x 104 9.05 x 106 cycle. Keywords : Bow Ramp Door; Stress; Fatigue Life; Finite Element; Ferry